PELAKSANAAN STANDAR OPERASIONAL PROSEDUR AUDIT, TANTANGAN HINGGA PELUANG AUDITOR DALAM MENINGKATKAN KUALITAS AUDIT PASCA COVID-19 - Rasyid Setiawan; Rudi Syaf Putra (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
In the current post-Covid-19 era that we are facing, auditors are confronted with a series of challenges. Changes in the business environment, shifts in risks, and alterations in how companies operate have affected the way audits are conducted. This research aims to investigate how the implementation of audit standard operating procedures, challenges, and opportunities faced by auditors contribute to improving audit quality post-Covid-19. Qualitative research methods are utilized in this article to explore and analyze various perspectives, concepts, and findings present in relevant literature. The data sources include primary and secondary data. Primary data is obtained from interviews conducted by the author with informants directly (face-to-face), while secondary data is derived from documents and previous research via Google Scholar, which can complement primary data and provide an overview in achieving the research objectives. The results indicate that the Covid-19 pandemic has impacted various aspects of the implementation of audit standard operating procedures, presenting challenges and opportunities for auditors to enhance audit quality post-Covid-19. The pandemic's impact on the business and financial landscape cannot be ignored, and auditors must be prepared to navigate these changes wisely. By understanding and responding to challenges and leveraging emerging opportunities, the auditing profession can continue to contribute to trust and transparency in corporate financial reporting in the future. In essence, audit quality will remain a cornerstone in safeguarding the integrity of financial markets post-Covid-19.